2015
DOI: 10.1109/tie.2015.2450736
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Prediction-Accuracy-Enhanced Continuous-Time MPC for Disturbed Systems via a Disturbance Observer

Abstract: This paper addresses the prediction accuracy enhancement problem in the context of continuous-time model predictive control (MPC) by using a disturbance observer. The disturbance estimation is introduced in the output prediction to correct the errors caused by disturbances and uncertainties, which eventually leads to the desired offset-free tracking performance. Due to such a different design philosophy, the computational burden of the proposed method will be significantly reduced as compared with the existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
125
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(125 citation statements)
references
References 39 publications
0
125
0
Order By: Relevance
“…On the other hand, it can be shown that the resultant optimal control does not depend on the values of q 1 and q 2 [23]. Therefore, one can choose q 1 = 1 and q 2 = 1 although both outputs are with different magnitudes.…”
Section: Continuous Nonlinear Predictive Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it can be shown that the resultant optimal control does not depend on the values of q 1 and q 2 [23]. Therefore, one can choose q 1 = 1 and q 2 = 1 although both outputs are with different magnitudes.…”
Section: Continuous Nonlinear Predictive Controlmentioning
confidence: 99%
“…Nowadays, the closed-form CNMPC becomes more mature and there exists a steadily increasing interest in real time implementation of this technique to nonlinear systems with fast dynamics such as electrical drives and power converters [23]. In [24], a composite controller consisting of CNMPC and a disturbance observer is implemented in real-time to a permanent magnet synchronous motor, and improved performance is reported.…”
Section: Introductionmentioning
confidence: 99%
“…The work [5], authored by Yang, et al, addresses the predication accuracy enhancement problem using continuous-time model predictive control and a disturbance observer. The disturbance estimate is introduced in the output prediction, which leads to the desired offset-free tracking performance.…”
Section: A Disturbance Observer Based Techniquementioning
confidence: 99%
“…Over the past few decades, due to its practical insights, the model predictive control (MPC) problem has attracted considerable research interest in systems with bounded disturbances, which gives rise to robust MPC (RMPC), see [4], [10], [17], [35] for discrete-time systems and [21], [26]- [28] for continuous-time systems. Up to date, RMPC strategy has been extensively applied into various engineering areas such as chemical process, power systems, DC motors and mobile robots [8], [10]- [14], [31], [36].…”
Section: Introductionmentioning
confidence: 99%